Westerly - Schutt, Will, 1981- (Yale series of younger poets, 2013)
A young soldier dons Napoleon's hat. An out-of-work man wanders Berlin, dreaming he is Peter the Great. The famous exile Dante finally returns to his native city to "hang his crown of laurels up." Familial and historical apparitions haunt this dazzling collection of poems by Will Schutt, the 2012 recipient of the prestigious Yale Series of Younger Poets award. Coupled with Schutt's own voice are the voices of some of Italy's most prominent nineteenth- and twentieth-century poets including Giacomo Leopardi, Alda Merini, Eugenio Montale, and Edoardo Sanguineti. Subtle, discerning, restrained, the poems in Westerly probe a vast emotional geography, with its contingent pleasures and pains, "where the door's always dark, the sky still blue." ... some narrow sickness buried you. Whatever boyhood I had fate hijacked too. Old friend, is this that world we stayed awake all night for? Truth dropped in. Far off, your cool hand points the way.